Differential dopaminergic modulation of executive control in healthy subjects - Roesch-Ely, Daniela; Scheffel, Hans; Weiland, Stephan; Schwaninger, Markus; Hundemer, Hans-Peter; Kolter, Thomas; Weisbrod, Matthias (Psychopharmacologia, 2005)
Executive control (EC) has different subcomponents, e.g., response inhibition (measured, for example, by the Stroop task) and working memory (WM-measured, for example, by delayed response tasks, DRT). EC has been associated with networks involving the prefrontal cortex (PFC). Moreover, there is evidence that dopamine agonists, especially those with a D1 profile, may modulate EC, since in the PFC D1 subtype receptors are more abundant. This study aimed to selectively distinguish whether D1 versus D2 dopamine agonism differentially influences EC related to the inhibition of irrelevant information and WM. Because of its D1 component, we predicted that the administration of pergolide (mixed D1/D2 agonist), in comparison with bromocriptine (D2 selective agonist) and placebo, would enhance performance in both EC tasks. Using a lateralized Stroop task, we predicted a decrease in the interference effect, as well as error rates, while no increase in facilitation effects. For the DRT task, we predicted fewer error scores in the delay condition. Forty male healthy subjects participated in this randomized, double-blind, placebo-controlled, crossover study. For the Stroop task no superiority of pergolide was found; however, with bromocriptine, decreased interference was found. No modulation of lateralization effects was shown in interference measures. Moreover, subjects on pergolide showed an absence of facilitation effects. No effects of either agonist were found for the DRT. Our findings suggest that dopamine agonists modulate two EC tasks differently. Furthermore, there seems to be a selective modulation of different aspects of the Stroop task.